Some Principles of Teaching Foreign Languages - Rakhimova Mexribon Ibragimovna (Genius Publishing Group, 2022)
The study of foreign languages in modern society is becoming an inseparable component of the professional training of specialists of various profiles, and the successful solution of professional growth issues and the expansion of contacts with foreign partners largely depend on the quality of their language training. Consequently, the school is designed to provide a certain level of foreign language proficiency, which could allow to continue its study during the period of university and postgraduate education, as well as independently. The success of training largely depends on the methodology of the teacher of a foreign language, on his ability to use various modern methods.
Keywords: affirmation; foreign language; methodology; insufficient